Implementation of the Philosophy for Children Approach to Build Critical Thinking Skills: A Case Study in Elementary School - Diki Somantri; Yusuf Tri Herlambang; Dinie Anggraeni Dewi (Universitas Negeri Malang, 2025)
Abstract: The 21st century demands critical thinking skills, a competence often underdeveloped by conventional elementary teaching methods. This creates a significant gap, particularly in contexts like Indonesia's Terdepan, Terluar, dan Tertinggal (3T) regions where students are vulnerable to misinformation. This qualitative case study thus aimed to analyze how the